2014
DOI: 10.1111/bcpt.12270
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin Promotes Apoptosis in Ovarian Cancer Cells via the iNOS/NO/STAT3/Survivin Signalling

Abstract: Arctigenin is a biologically active lignan extracted from the seeds of Arctium lappa and shows anticancer activity against a variety of human cancers. The aim of this study was to determine the effects of arctigenin on ovarian cancer cell proliferation and survival and associated molecular mechanisms. Human ovarian cancer OVCAR3 and SKOV3 cells were treated with arctigenin, and cell proliferation and apoptosis were assessed. Western blot analysis was used to examine signal transducer and activator of transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 24 publications
0
42
1
Order By: Relevance
“…Concordantly, arctigenin-mediated apoptosis was significantly inhibited by pretreatment of the U87MG and T98G cells with Z-DEVD-FMK, a caspase-3 inhibitor, indicating that the arctigenin-induced apoptosis of glioma cells may be mediated via caspase-3 activation. The pro-apoptotic activity of arctigenin has also been demonstrated in numerous other types of cancer, including breast and ovarian cancer (8,10,20).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Concordantly, arctigenin-mediated apoptosis was significantly inhibited by pretreatment of the U87MG and T98G cells with Z-DEVD-FMK, a caspase-3 inhibitor, indicating that the arctigenin-induced apoptosis of glioma cells may be mediated via caspase-3 activation. The pro-apoptotic activity of arctigenin has also been demonstrated in numerous other types of cancer, including breast and ovarian cancer (8,10,20).…”
Section: Discussionmentioning
confidence: 96%
“…Arctigenin has demonstrated anticancer activities in numerous types of cancer, including gastric cancer (8), breast cancer (9) and ovarian cancer (10). However, the effects of arctigenin on the aggressive phenotypes of human glioma cells remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The 10 most studied transcription factors and their relevant binding sites are shown in figure 1. The functional binding sites for Sp1 (Chen et al, 2011; Cheng et al, 2012; Zhang et al, 2015), NF-κB (Angileri et al, 2008; Papanikolaou et al, 2011; Wang et al, 2010), Stat3 (Huang et al, 2014; Kim et al, 2016), Rb (Raj et al, 2008; Yang et al, 2008), p53 (Vaziri et al, 2005; Zhou et al, 2002), and Egr1 (Wagner et al, 2008b) have been found in BIRC5 gene promoter, suggesting a possible involvement of these factors in direct control of BIRC5 gene expression. Among them, Sp1, Stat3 and NF-κB activate expression of BIRC5 gene.…”
Section: Transcriptional Factors Binding To the Promoter Region Ofmentioning
confidence: 99%
“…Arctigenin, a ligand isolated from the seeds of Arctium lappa, shows antiproliferative activities against a series of cancers [187][188]. A study illustrates the mechanism of its anticancer effect [188].…”
Section: Arctigenin (2)mentioning
confidence: 99%
“…A study illustrates the mechanism of its anticancer effect [188]. The results showed that arctigenin executed its antitumor effect by inhibiting STAT3 phosphorylation and survivin expression.…”
Section: Arctigenin (2)mentioning
confidence: 99%